Komparasi Tingkat Aksesibilitas Jaringan Transportasi Publik bagi Pekerja Ulang-Alik di Kawasan Surabaya Metropolitan Area - Salsa Shabrina; Siti Nurlaela (Diponegoro University, 2021)
The movement of commuter workers in Surabaya Metropolitan Area is dominated by private transportation modes users. Most commuter workers do not use public transportation for several accessibility reasons, such as long travel time (33.9%) and less practicality (32.7%). Previous research has been undertaken to encourage modal shifting from the perspective of workers as travelers. This type of researches emphasis more on exploring what factors can be intervened in order to make a modal shift from private vehicles to public transportation. What is not yet known is what causes the lack of competitiveness of public transportation. Namely, there are no studies that measure the level of accessibility of the public transportation network and the factors that influence it. This study aims to determine the factors that affect accessibility of public transportation networks for commuter workers in Surabaya Metropolitan Area based on a comparison of the level of accessibility in Sidoarjo-Surabaya and Gresik-Surabaya areas. The results of the study show that the level of accessibility in Surabaya Metropolitan Area is influenced by travel impedances, public transport routes, travel times, and the frequency of public transportation. Accessibility in Sidoarjo-Surabaya area can be improved by adding 1 public transport route in Gedangan District and increasing the frequency of public transportation to 4 units per hour in Waru and Sedati Districts. Whereas in Gresik-Surabaya area, accessibility can be improved through the addition of 1 public transport route in Menganti District and increasing the frequency of public transportation to 4 units per hour in Cerme District.